The Effect of Ecentric Load on The Carrying Capacity Rectangular Foundation on Clay - Querida Addisty Prasetyo; Adinda Misela; Miladatul Khofifah; Apta Kania Damayanti; Himatul Farichah (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
TThe foundation is part of the structure that directly functions to transmit the load from the weight of the structure above it to the ground. In this study, a rectangular foundation is used which is placed on clay soil with 3 variations in dimensions and 7 variations in eccentricity loading. This data will be used in finding the ultimate bearing capacity value. The purpose of this study was to determine the effect of eccentricity loads on the bearing capacity of rectangular foundations on clay soil types. The method used is the Meyerhof method (1963). The results obtained are the magnitude of the value of the bearing capacity of the foundation in each variation of its dimensions which is influenced by the eccentricity of the load. The conclusion of this study is that the bearing capacity of the foundation can be viewed from the coordinates of the axis of the foundation which is affected by the eccentricity of the load. The greater the eccentricity of the load received by the y-axis, the greater the value of the ultimate bearing capacity of the foundation. Meanwhile, the greater the eccentricity load received by the x-axis, the smaller the ultimate bearing capacity value.